Effect of irrigation management and plant population on herbaceous cotton yield - Oliveira, Francisco Assis de; Bezerra, José Renato Cortez; Oliveira, Bernadete Campos (Pesquisa Agropecuaria Brasileira, 1999)
In an alluvial soil, silt loam, of Açu valley, in the state of Rio Grande do Norte, Brazil, a research was carried out to study the effect of time of the last irrigation and plant population on yield and plant height of the herbaceous cotton (Gossypium hirsutum L.r. latifolium Hutch) cultivar. Acala del cerro. Treatments consisted of times of the last irrigation at 65, 80, 95 and 110 days after emergence and populations with 30,000, 60,000, 90,000 and 120,000 plants/ha. The experimental plan was a randomized complete blocks in a split-plot design, with four replications. Delaying time of last irrigation increased height and plant populations. A significant effect (P £ 0.01) of interaction between time of last irrigation and plant population was found for cotton yield. The highest cotton yield (4,090 kg/ha) was obtained with the interaction between time of last irrigation at 95 days and in population of 90,000 plants/ha. Irrigation time at 65 and 80 days were considered too early, and 110 days too late for cotton yields.